Structure and variability of the Pechora plume in the southeastern part of the Barents Sea - Rogozhin, Vladimir; Osadchiev, Alexander; Konovalova, Olga (Frontiers in Marine Science, 2023)
The Pechora River forms the large Pechora River plume in the southeastern part of the Barents Sea (also called the Pechora Sea). Many previous works addressed water masses in the Barents Sea, however, the Pechora plume received relatively little attention, therefore, many basic aspects of its structure and variability remain unknown. In this study, we focus on spreading of the Pechora plume in the Pechora Sea during ice-free periods. Based on the extensive in situ measurements and satellite observations, we describe the dependence of area and spatial characteristics of the Pechora plume on wind forcing, river discharge rate, and spring ice conditions. We reveal three general types of Pechora plume spreading, which are determined by the external forcing conditions. Joint analysis of a large set of in situ and satellite data provided opportunity to study the variability of the Pechora plume on the synoptic, seasonal, and interannual time scales. We reveal regular advection of the Pechora plume through the Kara Strait into the Kara Sea. In addition, we describe formation of a significant area of increased salinity within the Pechora plume formed during wind-induced coastal upwelling events. The results of this research are of key importance for understanding the physical, biological, and geochemical processes in the Pechora Sea and the adjacent areas of the Barents and Kara seas.